Social innovation from the institutions of higher education in Medellín, Antioquia: A conceptual view [La innovación social desde las instituciones de educación superior en Medellín - Antioquia: Una mirada conceptual] (2017)
The present article investigates the concepts of social innovation in the framework of Higher Education Institutions from the global context and developed in the Department of Antioquia. The methodology is qualitative and consists of a literature review in the national and international scope, interviews with influential actors such as managers, researchers and key managers of social innovation in Medellin as the Network of Social Innovation from Higher Education (RISES). The results show that the Metropolitan Area of the Valley of Aburrá are located the Universities, nodes and networks, which are in charge of leading the Plan of Science, Technology and Innovation, with the help of the Corporación Ruta N, as guidance of Processes at the local and national levels.